2010
DOI: 10.1105/tpc.110.076406
|View full text |Cite
|
Sign up to set email alerts
|

The Chlorella variabilis NC64A Genome Reveals Adaptation to Photosymbiosis, Coevolution with Viruses, and Cryptic Sex  

Abstract: Chlorella variabilis NC64A, a unicellular photosynthetic green alga (Trebouxiophyceae), is an intracellular photobiont of Paramecium bursaria and a model system for studying virus/algal interactions. We sequenced its 46-Mb nuclear genome, revealing an expansion of protein families that could have participated in adaptation to symbiosis. NC64A exhibits variations in GC content across its genome that correlate with global expression level, average intron size, and codon usage bias. Although Chlorella species hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
357
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 457 publications
(379 citation statements)
references
References 68 publications
7
357
0
Order By: Relevance
“…However, the occurrence of axonemal inner dynein arm heavy chain genes in Ostreococcus has been reported, raising the possibility that loss of ciliary components is incomplete and that remnants of a cilium might still exist (Wickstead and Gull, 2007). Alternatively, as suggested for Chlorella, which encodes nearly all ciliary outer dynein arm components (and a PAM gene), some green algae might have cilia at specific developmental stages that have not yet been observed; indeed, many cilia-related genes that are absent in land plants are conserved in these algae (Blanc et al, 2010).…”
Section: Pam Is Included In a Conserved Set Of Golgi And Cilia Proteinsmentioning
confidence: 99%
“…However, the occurrence of axonemal inner dynein arm heavy chain genes in Ostreococcus has been reported, raising the possibility that loss of ciliary components is incomplete and that remnants of a cilium might still exist (Wickstead and Gull, 2007). Alternatively, as suggested for Chlorella, which encodes nearly all ciliary outer dynein arm components (and a PAM gene), some green algae might have cilia at specific developmental stages that have not yet been observed; indeed, many cilia-related genes that are absent in land plants are conserved in these algae (Blanc et al, 2010).…”
Section: Pam Is Included In a Conserved Set Of Golgi And Cilia Proteinsmentioning
confidence: 99%
“…is considered evidence for sexual reproduction (Schurko and Logsdon 2008). Also, in certain algae where sexual reproduction is very rarely observed (Trebouxiophyceae: Blanc et al 2010, Fučíková et al 2015, or has not yet been observed (Ostreococcus: Derelle et al 2006;Micromonas: Worden et al 2009), homologues of these core meiotic genes are present (Grimsley et al 2010).…”
Section: A Molecular Perspective On Fertility Genetic Controlmentioning
confidence: 99%
“…If the chlorovirus K + channel genes were acquired from their algal host, one would expect that coevolution occurred between the virus and host K + channel-encoded genes. This assumption of coevolution was recently tested experimentally because the genomes of two algal virus hosts, C. variabilis (Blanc et al, 2010) and E. siliculosus (Cock et al, 2010), have been sequenced and annotated. The coccal green alga Chlorella spp.…”
Section: Origin Of Chlorovirus K + Channelsmentioning
confidence: 99%